El Tigre - Yearbook 2003 - Hale, Linda; O'Niell, Mary; Vertovec, Tom (Raton, NM Raton High School, 2003)
A presentation of the staff, classes, organizations, sports teams and events of the 2002-2003 school year.
Keywords: High School Yearbooks -- Raton, NM; Annuals -- Raton, NM